The big book of Christian apologetics : an A to Z guide - Geisler, Norman L.; Geisler, Norman L. (Grand Rapids, MI : Baker Books, 2012)
Can you explain your faith? In our pluralistic, post-Christian world, the need to be able to clearly and confidently explain why you believe what you believe has never been greater. "The Big Book of Christian Apologetics" is a comprehensive resource designed to equip you with information to help you defend and explain your faith to anyone, anywhere. Examining nearly every key issue, person, and concept related to Christian apologetics, this helpful book clarifies difficult biblical passages clearly explains various philosophical systems and concepts examines contemporary issues and challenges offers classic apologetic arguments It gives you the background you need to intelligently and persuasively talk about your Christian faith with skeptics and seekers in private or in the public square.
Includes bibliographical references (p. 605-642) and indexes.
Keywords: Apologetics -- Encyclopedias